2016
DOI: 10.1177/2156869316641730
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Trauma, Arrest, and Incarceration History among Black Americans

Abstract: Prior research indicates an association between exposure to trauma (e.g., being victimized) and perpetration of crime, especially in the context of chronic victimization. This study examines the relationship between trauma exposure, posttraumatic stress disorder (PTSD), and history of arrest and incarceration among a representative sample of black Americans from the National Survey of American Life (N = 5,189). One-third had a history of arrest, and 18 percent had a history of incarceration. Frequency of traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 76 publications
(111 reference statements)
3
58
0
Order By: Relevance
“…7 A third argument for tethering anti-violence objectives to criminal reform initiatives concerns the criminogenic nature of the experience of interpersonal violence: Violence survivors are notably over-represented among arrestees, prisoners, and exprisoners, even after controlling for poverty and other risk factors ( Jaggi et al 2016, Neller et al 2006, Western 2015, Wolff et al 2009). Indeed, the popular juxtaposition of (innocent) crime victims and the (guilty) justice-involved is entirely mythical: The people, families, and neighborhoods who suffer the burden of violence are also most harmed by mass incarceration.…”
Section: Should Criminal Justice Reformers Also Target Crime and Violmentioning
confidence: 99%
“…7 A third argument for tethering anti-violence objectives to criminal reform initiatives concerns the criminogenic nature of the experience of interpersonal violence: Violence survivors are notably over-represented among arrestees, prisoners, and exprisoners, even after controlling for poverty and other risk factors ( Jaggi et al 2016, Neller et al 2006, Western 2015, Wolff et al 2009). Indeed, the popular juxtaposition of (innocent) crime victims and the (guilty) justice-involved is entirely mythical: The people, families, and neighborhoods who suffer the burden of violence are also most harmed by mass incarceration.…”
Section: Should Criminal Justice Reformers Also Target Crime and Violmentioning
confidence: 99%
“…Generally, non-white boxers face greater risk of exposure to adverse environmental factors during their life time, away from boxing. A study on racial victimisation using the National Survey of Americans has revealed that up to a third of blacks had a history of arrest, 18% had been incarcerated, and their frequent exposure to traumas was associated with arrest and imprisonment [50]. We found substance abuse to occur across ethnic groups and occupations while convictions were higher among the nonwhite group.…”
Section: Social Inequalitiesmentioning
confidence: 61%
“…69 Provide Trauma-Informed Care Recent studies show 88% to 96% of men and women already in jail diversion programs reported significant trauma history prior to incarceration. 70,71 According to the SAMHSA, trauma is "an almost universal experience among people who use public mental health, substance abuse, and social services, as well as people who are justice-involved or homeless." 18 Multiple studies demonstrate that a significant number of individuals with an SMI also warrant a diagnosis of posttraumatic stress disorder (PTSD), although a minority are diagnosed with any trauma-related co-occurring disorder.…”
Section: Treat Substance Abuse Disordersmentioning
confidence: 99%